Combinatorial approach of in silico and in vitro evaluation of MLH1 variant associated with Lynch syndrome like metastatic colorectal cancer. Issue 6 (3rd June 2020) - Saleem, Komal; Zaib, Tahir; Ji, Wei; Zhang, Chunhui; Qin, Qian; Wang, Yusi; Xu, Lidan; Yu, Hanfei; Zhu, Siqi; Dong, Kexian; Si, Shuhan; Jia, Xueyuan; et al.
Abstract: Colorectal cancer (CRC) is the third most developing cancer worldwide and Lynch syndrome (LS) accounts for 3–4% of CRC. Genetic alteration in any of DNA mismatch repair (MMR) gene is the major cause of LS that disrupt the normal upstream and downstream MMR events. Germline mutation of MLH1 in heterozygous state have an increased risk for CRC. Defective MMR pathway mostly results in microsatellite instability (MSI) that occurs in high percentage of CRC associated tumors. Here, we reported a patient with LS like metastatic CRC (mCRC) associated with other related cancers. Whole exome sequencing (WES) of the proband was performed to identify potential causative gene. Genetic screening validated by Sanger sequencing identified a heterozygous missense mutation in exon 12 of MLH1 (c.1151T>A, p.V384D). The clinical significance of identified variant was elucidated on the basis of clinicopathological data, computational predictions and various in vitro functional analysis. In silico predictions classified the variant to be deleterious and evolutionary conserved. In vitro functional studies revealed a significant decrease in protein expression because of stability defect leading to loss of MMR activity. Mutant residue found in MutL transducer domain of MLH1 that localized in the nucleus but translocation was not found to be significantly disturbed. In conclusion, our study give insight into reliability of combinatorial prediction approach of in silico and in vitro expression analysis. Hence, we highlighted the pathogenic correlation of MLH1 variant with LS associated CRC as well as help in earlier diagnosis and surveillance for improved management and genetic counselling.